2022
DOI: 10.3390/membranes12050472
|View full text |Cite
|
Sign up to set email alerts
|

Green Chemistry and Molecularly Imprinted Membranes

Abstract: Technological progress has made chemistry assume a role of primary importance in our daily life. However, the worsening of the level of environmental pollution is increasingly leading to the realization of more eco-friendly chemical processes due to the advent of green chemistry. The challenge of green chemistry is to produce more and better while consuming and rejecting less. It represents a profitable approach to address environmental problems and the new demands of industrial competitiveness. The concept of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 280 publications
0
10
0
Order By: Relevance
“…The MIP was produced principally from poly­(vinyl alcohol), a biocompatible and biodegradable polymer ultimately derived from acetic acid and ethylene, both of which are readily obtained from biological sources. The atom economy of the synthesis is effectively 100%, with no waste material. This is highly beneficial from both an economic and an environmental perspective …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The MIP was produced principally from poly­(vinyl alcohol), a biocompatible and biodegradable polymer ultimately derived from acetic acid and ethylene, both of which are readily obtained from biological sources. The atom economy of the synthesis is effectively 100%, with no waste material. This is highly beneficial from both an economic and an environmental perspective …”
Section: Discussionmentioning
confidence: 99%
“…This is highly beneficial from both an economic and an environmental perspective. 1 Preliminary studies suggested that a template−polymer ratio of 25% (m/m) in synthesis was optimal for sensor performance. This is consistent with the literature for imprinted polymers of this kind.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on their strong recognition ability, high selectivity, and good stability, MIPs are extensively used in various fields such as solid phase extraction and analytical detection. In addition, MIPs are expected to achieve industrial production and application in environmental monitoring, the food industry, clinical medicine, natural products, and other industries [ 106 , 107 , 108 , 109 ]. According to the difference in templates, the latest progress in the recognition applications of MIPs in metal ions, organic molecules, and biological macromolecules was summarized.…”
Section: Application Progress Of Imprinted Polymersmentioning
confidence: 99%
“…Due to the wide variety and designable of intermolecular interactions, the most widely used imprinting materials are still the recognition and detection of various organic molecules, including synthetic and natural drugs, dyes, chemical materials, additives, etc. [ 106 , 107 , 108 , 109 ]. Many OMIPs have been introduced in the section on MIPs classification and preparation; here, we mainly summarize the latest application ( Table 6 ).…”
Section: Application Progress Of Imprinted Polymersmentioning
confidence: 99%